O desempenho motor e a percepção de competência de escolares com idade entre 7 e 10 anos - Buzzo, Viviane Aparecida dos Santos (2009)
This study investigated motor development and perceived competence associating the variables and comparing age groups. Five hundred and eighty one children participated in the study aging from 7 to 10 years, enrolled in 1st to 4th grades, from fundamental teaching schools of the public teaching network from the city of Maringá/PR. Motor performance evaluation was analyzed through Batteries II and III of the Movement Assessment Battery for Children (M-ABC) by Henderson and Sugden (1992). Perceived competence of children aging 7 years was verified through the Pictorial Scale of Perceived Competence and Acceptance for Young Children by Harter and Pike (1984) and perceived competence of children aging 8 to 10 years was identified through the Self Perception Profile for Children test by Harter (1985). Data analysis was performed through the tests: Shapiro-Wilk, Anova One-Way, Bonferroni, Kruskall-Wallis, Mann-Whitney, Anova repeated measures and fisher's exact, adopting 5% of significance. The results indicate 78,1% of children with Typical Motor Developmental (DMT), 10,5% of children with Development Coordination Disorder risk (ZP) and 11,4% of children diagnosed with Development Coordination Disorder (TDC). As for the comparison between motor performances among ages, it was verified to children with DMT higher motor performance to 8 year old children and to TDC children, better performance for 8 and 9 year old children. The motor performance types of difficulties analysis between age groups revealed non-similar results to the children, however, for motor performance total score 8 year old children demonstrated higher motor performance than children from other ages. As for the differences found between motor abilities referring to the children was verified that 7 to 10 year old showed motor difficulties in manual dexterity tasks. School, social and athletic perceived competence demonstrated predominance (approximately 95%) of 7 years old children, for DMT as for children who showed ZP and TDC, for high perceived competence. Children from 8, 9 and 10 years age line demonstrated a predominance of high perceived competence for school competence. As for thletic competence the perception varied from high for 8 and 10 year old children to moderate to 9 year old children. And, considering the association between motor performance and perceived competence, it was observed a significantb association between motor performance and athletic competence for 8 year old children, and motor performance and social competence for 10 year old children. So it is concluded that the level of ability acquisition is variable and that motor development occurs by environmental stimulation and task specificity associated to individual's particularities. As for perceived competence, 7 year old children demonstrated to be highly competent while 8 to 10 year old children showed more precise perceived competence, judging more accurately one's motor performance.